Impact of Online Learning in India: A Survey of University Students During the COVID-19 Crisis - Manash Pratim Goswami; Jyoti Thanvi; Soubhagya Ranjan Padhi (Asian Journal for Public Opinion Research)
The unprecedented situation of COVID-19 caused the government of India to instruct educational institutions to switch to an online mode to mitigate the losses for students due to the pandemic. The present study attempts to explore the impact of online learning introduced as a stop-gap arrangement during the pandemic in India. A survey was conducted (N=289), via Facebook and WhatsApp, June 1-15, 2020 to understand the accessibility and effectiveness of online learning and constraints that students of higher education across the country faced during the peak times of the pandemic.